Distribusi Filariasis Brugia timori dan Wuchereria bancrofti di Desa Kahale, Kecamatan Kodi Balaghar, Kabupaten Sumba Barat Daya, Nusa Tenggara Timur - Rais Yunarko; Yona Patanduk (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2016)
Lymphatic filariasis is still a health problem in the East Nusa Tenggara province. Southwest Sumba District is filariasis endemic area. It is found 35 chronic cases in Kodi Balaghar subdistrict. Although implementation of mass drug adminsitration was held in 2011 but drug coverage had been poor and not reach Kodi Balaghar subdistrict. The purpose of this study were to measure the prevalence and distribution, determine the density and type of parasite and mapping cases in the Kodi Balaghar subdistrict. This research was a descriptive study with cross sectional approach which conducted in the Kahale Village, Kodi Balaghar Subdistrict in 2012. Five hundred people were checked. The results of the examination found that 21 positive microfilariae cases, Mf rate was 4.2%. Two species of microfilariae that found were Wuchereria bancrofti and Brugia timori. The distribution filariasis cases is higher in men and higher in reproductive age (15-45 years). There were three types of infection, an infection by B. timori, W. bancrofti, and mixed infections both the microfilariae. The density of microfilariae in the area was 190.86 mf/ml, the density W. bancrofti was 160.04 mf/ml, B. timori was 115.97 mf/ml. Filariasis cases distributed near to potential breeding places of mosquito .